Movements and diurnal behaviour patterns in a Baltic grey seal ( Halichoerus grypus ) - SJOBERG, M; FEDAK, M A; MCCONNELL, B J (Polar Biology, 1995)
A sub-adult grey seal was caught and tagged with a satellite relay data logger at Tihallan (61 degrees 28'00''N, 17 degrees 25'40''E), Sweden, on 21 August 1992. We tracked it for 115 days during which time we recorded 841 locations, data on 3556 dives and 80 ''haulout'' periods. It travelled 730 km in the first 12 days to the southern Archipelago Sea. It stayed most of the remaining time within 25 km of a haulout site, with a major exception of an 8-day trip of 520 km. Dive shape and swimming activity were used to distinguish dive types. Square-shaped ''foraging'' dives were more common over the midday period. ''Haulout'' periods were more common during the night.